Tanggapan Siswa terhadap Model Pembelajaran Cooperative Learning Tipe Jigsaw dan hubungannya dengan Prestasi Kognitif Mereka pada Bidang Studi PAI - Taufiqurrahman Taufiqurrahman (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2020)
This study aims to: (1) find out the reality of students' responses to the cooperative learning model of jigsaw type; (2) knowing the reality of students' cognitive achievement in the field of PAI study; (3) to find out the reality of the relationship between students' responses to the Jigsaw type cooperative learning model and their cognitive achievement in the field of PAI study. The method used in this research is descriptive method. The sample in this study was taken 10% of the population of 464 people to 46 students. Sampling of 46 students was determined purposively by the researcher and focused on class VII C of SMPN